(untitled) - Walstad, William B. (Boston, 2008)
One of the world’s leading experts on economic education, William Walstad of the University of Nebraska-Lincoln, has prepared the seventeenth edition of the Study Guide. Many students find the Study Guide indispensable. Each chapter contains an introductory statement, a checklist of behavioral objectives, an outline, a list of important terms, fill-in questions, problems and projects, objective questions, and discussion questions. The answers to Economics’ end-of-chapter Key Questions appear at the end of the Study Guide, along with the text’s glossary. The Guide comprises a superb “portable tutor” for the principles student. Separate Study Guides are available for the macro and micro paperback editions of the text.
Keywords: Macroeconomics,Kinh tế vĩ mô; Problems, exercises, etc.,Câu hỏi, bài tập,...